Geological criteria for waste disposal site selection: a case study from Kanichadar, Dhangarhi, Far Western Nepal - Rimal, Lila Nath; Jnawali, Bharat M.; Manandhar, Surya Prakash (Journal of Nepal Geological Society, 2002)
Proper management of municipal solid waste in an environmentally friendly way needs first-hand knowledge of site geology. A clay layer (i.e. geological barrier) of sufficient thickness and extension beneath the surface is a suitable condition for a sanitary landfill site. The clay layer acts as a natural barrier against the migrating pollutants originating from leachate into the ground. The leachate generated at the landfill site can pollute the groundwater in absence of such geologic barrier. The Kanichadar area is underlain by about 3 m thick fine-grained soil. The topmost soil layer is 20-50 cm thick dark brown organic clay. There is a highly compact, dark brown and dry inorganic clayey silt layer of more than 1.5 m thickness below the organic clay layer. Soil samples collected from different Auger holes were subjected to laboratory analysis to determine their physical and chemical properties. The values thus obtained indicated that the soil belongs to 'CL' type, implying that the soil is inorganic clay of low to medium plasticity. However, the hydrometer analysis showed that the samples were of clayey silt. The cation exchange capacity (CEC) values obtained from the depth of 0.5-2.30 m revealed that the soil had moderate to high barrier potential for attenuation of the migrating pollutants. Therefore, the area close to these auger holes was found to be suitable for sanitary landfill.